KOMUNIKASI DAN INTOLERANSI POLITIK - Firman Alamsyah Taufik Robbi (Dialektika, 2016)
The essence of democracy is to put people as the highest sovereign in deciding how best a country organized through political participation was active , free and voluntary. The problem is the engagement , it was not enough in Indonesia given the remnants of authoritarianism in the past turned out to form a political personality that is intolerant and reflected on the conflict surrounding the election of the leadership of the executive board. Within this framework , communication as a means of transmission , transaction and interaction symbol - a symbol that means playing a role through the identification and dissemination of feeling threatened social education modality , thereby building the perception of power contestation program more as compared to a mere struggle for power problems.